The neutral amino acid transporter SLC7A10 in adipose tissue, obesity and insulin resistance - Jersin, Regine Åsen; Jonassen, Laura Roxana; Dankel, Simon Nitter (Frontiers in Cell and Developmental Biology, 2022)
Obesity, insulin resistance and type 2 diabetes represent major global health challenges, and a better mechanistic understanding of the altered metabolism in these conditions may give improved treatment strategies. SLC7A10, a member of the SLC7 subfamily of solute carriers, also named ASC-1 (alanine, serine, cysteine transporter-1), has recently been implicated as an important modulator of core processes in energy- and lipid metabolism, through its particularly high expression in adipocytes. In human cohorts, adipose SLC7A10 mRNA shows strong inverse correlations with insulin resistance, adipocyte size and components of the metabolic syndrome, strong heritability, and an association with type 2 diabetes risk alleles. SLC7A10 has been proposed as a marker of white as opposed to thermogenic beige and brown adipocytes, supported by increased formation of thermogenic beige adipocytes upon loss of Slc7a10 in mouse white preadipocytes. Overexpression of SLC7A10 in mature white adipocytes was found to lower the generation of reactive oxygen species (ROS) and stimulate mitochondrial respiratory capacity, while SLC7A10 inhibition had the opposite effect, indicating that SLC7A10 supports a beneficial increase in mitochondrial activity in white adipocytes. Consistent with these beneficial effects, inhibition of SLC7A10 was in mouse and human white adipocyte cultures found to increase lipid accumulation, likely explained by lowered serine uptake and glutathione production. Additionally, zebrafish with partial global Slc7a10b loss-of-function were found to have greater diet-induced body weight and larger visceral adipocytes compared to controls. However, challenging that SLC7A10 exerts metabolic benefits only in white adipocytes, suppression of SLC7A10 has been reported to decrease mitochondrial respiration and expression of thermogenic genes also in some beige and brown adipocyte cultures. Taken together, the data point to an important but complex role of SLC7A10 in metabolic regulation across different adipose tissue depots and adipocyte subtypes. Further research into SLC7A10 functions in specific adipocyte subtypes may lead to new precision therapeutics for mitigating the risk of insulin resistance and type 2 diabetes.